2021
DOI: 10.1111/1751-7915.13883
|View full text |Cite
|
Sign up to set email alerts
|

Mining and engineering exporters for titer improvement of macrolide biopesticides in Streptomyces

Abstract: Exporter engineering is a promising strategy to construct high-yield Streptomyces for natural product pharmaceuticals in industrial biotechnology. However, available exporters are scarce, due to the limited knowledge of bacterial transporters. Here, we built a workflow for exporter mining and devised a tunable plug-and-play exporter (TuPPE) module to improve the production of macrolide biopesticides in Streptomyces. Combining genome analyses and experimental confirmations, we found three ATPbinding cassette tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…This module was implemented in industrial S. avermitilis NEAU12, resulting in a 53% improvement of avermectin B1a production. 202…”
Section: Metabolic Regulation and Biosynthesis Of Potential Nematicid...mentioning
confidence: 99%
See 1 more Smart Citation
“…This module was implemented in industrial S. avermitilis NEAU12, resulting in a 53% improvement of avermectin B1a production. 202…”
Section: Metabolic Regulation and Biosynthesis Of Potential Nematicid...mentioning
confidence: 99%
“…This module was implemented in industrial S. avermitilis NEAU12, resulting in a 53% improvement of avermectin B1a production. 202 4.1.3 Biosynthetic gene cluster (BGC) manipulation. In general, the manipulation of biosynthetic gene clusters includes deletion, insertion, point mutation and substitution of genes (or modules), which stimulates the production of specic or new products.…”
Section: Reviewmentioning
confidence: 99%
“…The heterologous biosynthesis of isoflavonoids faces issues of a low titer and low yield. Following the development of a microbial strain capable of the de novo biosynthesis or biotransformation of an isoflavonoid of interest, efforts, i.e., directed evolution, and engineering of primary metabolism are put forward to improve the final yield [12,17]. It has been reported that the glycosylation of the end-product improves its heterologous biosynthesis rate; therefore, the addition of a UGT gene in the pathway to glycosylate the isoflavonoid of interest is a unique approach to enhance the final yield [18].…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al built a step-by-step workflow based on the TCDB database BLAST, and they included substrate analysis, transporter classification analysis, and phylogenetic analysis to mine BGC-independent exporters. Together with a tunable plug-and-play exporter module with replaceable promoters and ribosome-binding sites, they realized the titer improvement of macrolide biopesticides in different Streptomyces producers [18]. Nevertheless, the current commonly used approaches are mainly sequence-dependent or based on known exporters, and the methods of BGC-independent exporter mining still need development.…”
Section: Introductionmentioning
confidence: 99%